The decision-making process of transferring patients home to die from an intensive care unit in mainland China: A qualitative study of family members' experiences. (June 2023) - Lin, Yanxia; Long-Sutehall, Tracy; Myall, Michelle
Abstract: Objectives: To map the decision-making process of family members involved in transferring a critically ill patient home to die from an intensive care unit in mainland China and to explore the experiences of those family members. Design: A constructivist qualitative study. Setting: One hospitals intensive care unit in Southeast China. Methods: Thirteen adult family members (of ten patients) who participated in decision-making related to transferring a relative home to die from the intensive care unit were purposively selected. Data were collected via interviews and analysed applying thematic analysis. Findings: A two-stage decision-making process was identified. Family decision-making was mediated by factors including: accepting the impending death and hope that the patient would not die; time pressures in which decisions had to be made, and the challenges of meeting cultural expectations of a home death. Transfer home was a family-centred decision constrained by a gender-based hierarchy restricting the involvement of different family members. Conclusion: The stages and key factors in the decision-making process of family members when involved in transferring a patient home to die from an intensive care unit in China are rooted and informed by cultural expectations and limits in the current healthcare system regarding end-of-life care options. Understanding the climate in which family members must make decisions will facilitate supportive interventions to be implemented by healthcare professionals. Further empirical research is needed to explore family members' needs when the patient has been transferred and dies at home in mainland China. Implications for Clinical Practice: Healthcare professionals need to understand the challenges family members face when deciding to transfer a relative home to die from an intensive care unit. For example time pressures can limit the choices of family members so that to provide them with timely, ongoing, realistic updates for a greater involvement of family members in generating end of life care plans could be beneficial. 1